Deletion of kinin receptor B2 enhances orthodontic tooth movement and alveolar bone remodeling - Natália Couto Figueiredo; Mitchell Piacsek; Carina Cristina Montalvany-Antonucci; Mariana de Souza Santos; Flávio Almeida Amaral; Mauro Martins Teixeira; Tarcília Aparecida Silva; Soraia Macari; Subramanya Pandruvada; Ildeu Andrade Jr (PLoS ONE, 2025)
The kallikrein-kinin system (KKS) is a complex enzymatic system involved in multiple biological processes, particularly inflammation. The system’s peptides exert broad effects through two receptors, B1 (B1R) and B2 (B2R), expressed in various cell types, including osteoblasts. However, the impact of this system on bone remodeling induced by mechanical force needs to be better understood. This study aimed to elucidate the role of the B2 kinin receptor in bone phenotype and remodeling under mechanical stress. Orthodontic forces were applied to the upper first molars of B2R−/− mice and wild-type controls. Bone parameters, bone cellular counts, expression of inflammatory biomarkers, and osteoblast and osteoclast differentiation and activity were assessed using microtomography, histological analysis, real-time polymerase chain reaction (qPCR), and in vitro bone cell cultures, respectively. The results revealed that B2 receptor deficiency significantly altered maxillary bone architecture, reduced trabecular thickness, increased orthodontic tooth movement, and spontaneous alveolar bone loss (ABL). Histological analysis showed a higher number of osteoclasts in B2R−/− mice, with no significant change in osteoblast counts. Molecular analysis indicated elevated levels of RANK, RANKL, OPG, RANKL/OPG, IL-1β, and B1 receptor expression in B2R−/− mice, while in vitro studies confirmed enhanced osteoclast numbers and activity in B2R−/− cells. In conclusion, this study underscores the critical roles of kinin receptors in regulating alveolar bone remodeling, with B2R deletion leading to increased osteoclastic activity and bone loss. The compensatory upregulation of B1Rs in the absence of B2Rs suggests functional redundancy. However, the B2R−/− phenotype emphasizes the complex involvement of the KKS pathway in bone physiology, suggesting avenues for further research into bone pathophysiology and potential therapeutic approaches.